The Polarity of Enclosed Spaces in the Poetry of Mohammad Afifi Matar; the Cases of “The House” and “The Prison” - hamed poorheshmati; shahriar hemati (دراسات فی اللغه العربیه و آدابها)
The spatial polarity or dichotomy is a new critical approach in recognizing the contradictions and differences of related place words, which play aesthetic functions in the text either obviously or in hidden manner. Closed spaces, due to the significant role that they play in Arab contemporary poetry, have various functions, such as cognitive-dramatic functions, and can familiarize the readers with the differential effects of the open and close places, spaciousness and confinement, introversion and extraversion, and other contradictions which result from internally and externally induced challenges and influence the quality of the poetic invention, and in turn result in a strong opposition of spatial terms. Mohammad Afifi Matar is a great poet of Egypt, whose poetry revolves around a set of contrasting elements with variable meanings, which by accommodating and capitalizing on place polar terms, incorporates different intrinsic and social issues. This research uses descriptive-analytic method and focuses on the polarity between house and prison in the poetry of Mohammad Afifi Matar. The results of this study show that the poet refers to the function of the house in contrasting ways, such as the confrontation between dream and tragedy, the opposition of its openness and its closed space. On the one hand he wants to digress from the external realities and its frustrating concerns towards the world of good memories, and on the other hand, he arouses the negative feelings of sadness and anxiety associated with house by using its position to the concept of land and defense of the homeland. The poet extends the concept of prison through the polarity of self and community; in the former he emphasizes the intensity of his suffering and psychological pressures, and in the latter on important social issues while he was in prison and before it.